2020
DOI: 10.1039/d0cc05126h
|View full text |Cite
|
Sign up to set email alerts
|

Design of spontaneously blinking fluorophores for live-cell super-resolution imaging based on quantum-chemical calculations

Abstract: Spontaneously blinking fluorophores are powerful tools for live-cell super-resolution imaging under physiological conditions. Here we show that quantum-chemical calculations can predict key parameters for fluorophore design. We applied this methodology...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 17 publications
1
32
2
Order By: Relevance
“…Previous studies demonstrated that HMSiR halo-tag ligands do not require special buffers or cellular growth media and are cell-permeable. 18,19 We optimized our probe and found that consistent with our previous results, 5 0 -isomer HMSiR-Hoechst conjugates stain the nucleus of living cells more efficiently than 6 0 -regioisomer HMSiR-Hoechst conjugates. 9 Furthermore, we demonstrate that a shorter linker (two -CH 2 -units) between HMSiR and Hoechst leads to highly efficient quenching of the fluorescence in the unbound state, increases affinity for DNA and allows no-wash SMLM imaging of DNA in living cells.…”
supporting
confidence: 81%
“…Previous studies demonstrated that HMSiR halo-tag ligands do not require special buffers or cellular growth media and are cell-permeable. 18,19 We optimized our probe and found that consistent with our previous results, 5 0 -isomer HMSiR-Hoechst conjugates stain the nucleus of living cells more efficiently than 6 0 -regioisomer HMSiR-Hoechst conjugates. 9 Furthermore, we demonstrate that a shorter linker (two -CH 2 -units) between HMSiR and Hoechst leads to highly efficient quenching of the fluorescence in the unbound state, increases affinity for DNA and allows no-wash SMLM imaging of DNA in living cells.…”
supporting
confidence: 81%
“…Our group recently also developed a quantum-chemical calculation-based method to predict the equilibrium constant and blinking kinetics of the intramolecular spirocyclization of novel compounds [45]. To develop spontaneously blinking, spirocyclic fluorophores the pKcycl value should be below 6, so that only a small subset of fluorophores exists in the open state at the physiological pH of 7.4 and the lifetime of the open form (τcycl) should be in the range of one to hundreds of milliseconds, to match the exposure time of the used microscopes [42].…”
Section: Computational Approachesmentioning
confidence: 99%
“…We previously determined the pH-value at which 50% of the molecules are present in the non-fluorescent form as the pK cycl value [43]. Chemical modification of the xanthene core, intramolecular nucleophiles, and the pendant aromatic ring can significantly alter that value [44,45]. This pK cycl value is especially important if the dye should be highly fluorescent at a certain pH, such as the physiological pH of 7.4 for example.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 Among the successful developments of the past decade, numerous triarylmethane fluorophores, in particular the rhodamine analogues with the oxygen bridge replaced with CMe 2 , SiMe 2 , GeMe 2 , and P(O)R groups to achieve bathochromic shifts of absorption and emission, have been reported. 4 However, the latest disclosures 5 show that the demand for chemical diversity of newly designed labels exceeds the scope of established synthetic chemistry of triarylmethane dyes, and the synthetic methods offering practicable yields are often lacking.…”
mentioning
confidence: 99%